X-ray fluorescence analysis of coastal sediments of Tamil Nadu with a statistical approach - Karthikayini, S.; Hamideen, Mefleh S.; Chandrasekaran, A.; Khandaker, Mayeen Uddin *; Bradley, D.A. * (Elsevier, 2023)
X-ray fluorescence spectroscopy is applied to determine the concentration of essential and toxic heavy metals such as silicon (Si), potassium (K), calcium (Ca), titanium (Ti), iron (Fe), copper (Cu), zinc (Zn), nickel (Ni), and lead (Pb) in the sediments of Kovalam coastal area, Tamil Nadu, India. Fe (599280 ppm), an essential heavy metal/mineral shows the highest average concentration, followed by Si (181593 ppm), Ca (130913 ppm), K (99673 ppm), Ti (77620 ppm), Cu (64 ppm), Ni (43 ppm), Pb (20 ppm), and Zn (8 ppm). Heavy metal contamination was assessed using various pollution indicators such as the geo-accumulation index (Igeo), contamination factor (CF), pollution load index (PLI), and enrichment factor (EF). Si, K, Ca, Ti, Fe, Cu, Ni, Pb, and Zn had mean Igeo values of −1.29, 1.54, 1.07, 3.59, 3.19, 0.64, −1.14, −0.22, and −3.70, respectively. Except for Ti (19.36) and Fe (13.87), the average CF value for determined heavy metals was significantly low. The PLI value ranges from 1.47 to 2.46. Heavy metal EF values are greater than 1 in all sampling locations. Multivariate statistical analyses such as Pearson correlation analysis, cluster analysis, and principal component analysis are performed to identify the sources of heavy metals in the studied sediment samples. The findings indicate that anthropogenic sources such as boating and tourism activities have a probable contribution on the enrichment of K, Ca, Ti, Fe, Cu, and Pb in sediments, necessitating more attention in monitoring of toxic heavy metals (such as Pb) contamination in the coastal environment.